The Use of Picture Cards as Teaching Media to Improve Speaking Ability of Eleventh Graders: A Classroom Action Research - Rizki Ambarwati; Nur Hayati (Masters in English Education, The Directory of Postgraduate Program,Universitas Muhammadiyah Malang, 2020)
English has been well-known as the global language since the last three decades. English is not only as a mean of international communication but as a tool to gain and exchange information as well. Therefore, English becomes the language taught the most in school. Learning language cannot be separated from language skills. Mastering 4 skills of language is important to be acknowledge as Language master. However, many students have difficulties in mastering the language skills, speaking especially. This condition may occur because of different reasons. The result of preliminary study showed that the students of XI MIPA 5 at SMA Negeri 4 Malang had lower score in speaking compared to other language skills. It was because they got difficulty in developing idea of what to say which then made them having no confidence in speaking. Moreover, they were also afraid of making mistake. Therefore, this Action Research was employed as the research design to improve the students’ ability in speaking. The subjects of this study were students of XI MIPA 5 science class which consists of 33 students. The research findings showed that the use of picture cards has progressively improved the students’ speaking ability proven by the improvement of their speaking score. There were 87.87% students could improve their score by at least 5 points. Using picture cards as teaching media helped the students to have a betterment of speaking skill. The result of the observation checklist and field note showed that using picture cards media in teaching cause and effect made students easier in understanding the material which then it helps them easier in doing the speaking performance.